치아홈메우기 시술에 대한 전주시 초등학교 학부모의 인식과 태도 - 김수진; Su Jin Kim; 이해진; Hae Jin Lee; 김영삼; Young Sam Kim; 전재규; Jae Kyu Jeon; 장기완; Kee Wan Chang (대한구강보건학회지, 2012)
Objectives: The aim of this study was to look at elementary school student parents` recognition of pit and fissure sealant, national health insurance application and recognition of and attitude toward dental hygienist`s treatment for pit and fissure sealant. Methods: The subject of study was parents of children in the 3rd and 4th grades at an elementary school in Jeonju city. To consider those parents` socio-economic factors of elementary school grade level classified by Education Office, ``A: highest socio-economic`` level and ``D: lowest socio-economic`` level, elementary school student parents were surveyed. In this study, a set of questionnaire was distributed to student`s parents, a total of 23 questions on recognition and attitude for pit and fissure sealant by national health insurance system, treatment of sealing by dental hygienist. The statistical analysis of the data collected was done by using SPSS 12.0. Results: Of the student parents, the percentage of those who recognized that national health insurance covers the pit and fissure sealant was 36.9% only. The percentage of parents who did not know was larger than that of those who knew. Of the student parents, those who had once or more received treatment of the pit and fissure sealant by dental hygienist were highly satisfied and their attitude were also very positive about dental hygienist`s ability to operate the pit and fissure sealant. Conclusions: The higher the recognition rate of pit and fissure sealant can be covered national insurance system, the lesser consumer`s burden.